Proceedings of the 2007 InSITE Conference 2007
DOI: 10.28945/3095
|View full text |Cite
|
Sign up to set email alerts
|

Befriending Computer Programming: A Proposed Approach to Teaching Introductory Programming

Abstract: The problems encountered by students in first year computer programming units are a common concern in many universities including Victoria University. A fundamental component of a computer science curriculum, computer programming is a mandatory unit in a computing course. It is also one of the most feared and hated units by many novice computing students who, having failed or performed poorly in a programming unit, often drop out from a course. This article discusses some of the difficulties experienced by fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
1
20
0
4
Order By: Relevance
“…In [6], authors confirmed that programming is a compulsory subject and an essential component in Computer Science curriculum, and that many novice learners often drop out from their degree courses due to either performing poorly or failing in programming subjects, which are considered the most hated and feared areas in a Computing qualification. In emphasizing the difficulty of the programming process, the reference clarified that programming techniques and skills are also hard to teach, not only because the traditional teaching methods are not very effective in the areas of scripting and problem solving, but also because such skills are best learned through experience.…”
Section: A Traditional Programmingmentioning
confidence: 94%
“…In [6], authors confirmed that programming is a compulsory subject and an essential component in Computer Science curriculum, and that many novice learners often drop out from their degree courses due to either performing poorly or failing in programming subjects, which are considered the most hated and feared areas in a Computing qualification. In emphasizing the difficulty of the programming process, the reference clarified that programming techniques and skills are also hard to teach, not only because the traditional teaching methods are not very effective in the areas of scripting and problem solving, but also because such skills are best learned through experience.…”
Section: A Traditional Programmingmentioning
confidence: 94%
“…This is because it requires more of individual's skills than knowledge (Sarpong, 2013;Hadjerrouit, 2008;Miliszewska and Tan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some students who struggle with programming may drop out of the course while others might choose a career path which does not involve programming (Miliszewska & Tan, 2007;Stamouli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%